Noise as a factor of environmental stress for cattle - Angrecka, Sabina; Solecka, Urszula; Vieira, Frederico Marcio Correa; Herbut, Piotr; Deniz, Matheus [UNESP]; Adamczyk, Krzysztof; Godyn, Dorota (Walter De Gruyter Gmbh, 2023)
One of the minor studied stress factors in cattle breeding is noise. Noise is any unwanted chronic or intermittent sound and the amount and type of noise sources are related to the cattle production system. The aim of the review was to highlight the literature regarding noise as a robust environmental stressor and the following impact on the behavioural, physiological and performance reactions of cattle. In addition, was showed how often this problem is discussed in the scientific literature. Review was conducted with a search strategy of peer-reviewed articles written in English before June 2022. The systematic searches were performed using the Web of Science and Scopus databases with the integration of Boolean operators to string together words or phrases. It is recommended to create an environment around cows in which the acoustic stimuli affecting the animals are under their control. Therefore, if the sound source cannot be eliminated, animals should be able to choose places with a lower sound intensity appropriate for the perceptual abilities of cattle. On the other hand, attention is paid to the positive aspects of some groups of sound signals i.e. positive nature of music for cows and people during milking. The scientific publications analysed by the methodology drew attention to the repeatability of the discussed results. Further research on this subject should be considered because developing farms use modern solutions in barns which can negatively affect the acoustic comfort of cows, and their impact has yet to be determined.
Keywords: environmental stressor; noise; dairy cattle; behaviour; freestall barns